Construction of Axially Chiral Arylpyrroles via Atroposelective Diyne Cyclization - Chen, Yang‐Bo; Liu, Li‐Gao; Chen, Can‐Ming; Liu, Yi‐Xi; Zhou, Bo; Lu, Xin; Xu, Zhou; Ye, Long‐Wu (Angewandte Chemie International Edition, 2023)
Axially chiral biaryls widely exist in natural products and pharmaceuticals and are used as chiral ligands and catalysts in asymmetric synthesis. Compared to the well‐established axially chiral 6‐membered biaryl skeletons, examples of 5‐membered biaryls have been quite scarce, and mono‐substituted 3‐arylpyrrole atropisomers have not been reported. Here, we disclose a copper‐catalyzed atroposelective diyne cyclization for the construction of a range of axially chiral arylpyrrole biaryls in good to excellent yields with generally excellent enantioselectivities via oxidation and X−H insertion of vinyl cations. Importantly, this protocol not only represents the first synthesis of mono‐substituted 3‐arylpyrrole atropisomers, but also constitutes the first example of atroposelective diyne cyclization and the first atropisomer construction via vinyl cations. Theoretical calculations further support the mechanism of vinyl cation‐involved cyclization and elucidate the origin of enantioselectivity. A novel copper‐catalyzed atroposelective diyne cyclization enables the efficient synthesis of a range of axially chiral arylpyrrole biaryls in good to excellent yields with generally excellent enantioselectivities via oxidation and X−H insertion of vinyl cations. This method gives the first synthesis of mono‐substituted 3‐arylpyrrole atropisomers and the first atroposelective diyne cyclization.